PRODUCTION OF FOUNDRY MATERIALS FOR AGRICULTURAL MACHINERY (Web of Technology: Multidimensional Research Journal, 2024)
This article discusses the manufacture of agricultural machinery parts by casting. Agricultural machinery casting parts are the most important component of modern agricultural equipment. That different types of castings depend on different application requirements. Each type serves a unique purpose and is vital for the efficient operation of agricultural machinery.